Bactericidal Efficacy of High Irradiance Ultraviolet A Photoactivation of Riboflavin Versus Standard Corneal Cross-Linking Protocol In Vitro. Issue 9 (30th September 2022) - Tarff, Andreina; Drew-Bear, Laura E.; Yee, Rebecca; Cano, Marisol; Zhang, Ying; Behrens, Ashley
Abstract : Purpose: The purpose of this study was to compare the efficacy of high ultraviolet A (UVA) irradiance photoactivation of riboflavin (vitamin B2) versus the standard corneal cross-linking protocol on bacterial viability. Methods: Methicillin-sensitive Staphylococcus aureus (MSSA) Newman strain and methicillin-resistant multidrug-resistant S. aureus (MDR-MRSA) USA300, CA409, CA127, GA656, and NY315 strains were exposed to a UVA energy dose of 5.4 to 6 J/cm 2 by 2 high irradiance regimens: A) 30 mW/cm 2 for 3 minutes and B) 10 mW/cm 2 for 10 minutes with B2 0.1%. Control groups included B2/UVA alone, CA409 exposed to standard B2 0.1% + UVA (3 mW/cm 2 for 30 minutes), and an untreated sample. Cell viability was assessed. Triplicate values were obtained. The Mann–Whitney test and Student t test were used for statistical analysis. Results: There was no difference comparing the median bacterial load (log CFU/mL) of the untreated samples versus regimen A: Newman P = 0.7, CA409 P = 0.3, USA300 P = 0.5, CA127 P = 0.6, GA656 P = 0.1, and NY315 P = 0.2 ( P ≥ 0.1); and B: Newman P = 0.1, CA409 P = 0.3, USA300 P = 0.4, CA127 P = 0.6, GA656 P = 0.1, and NY315 P = 0.3 ( P ≥ 0.1). Standard regimen killed 100% of CA409. Conclusions: Photoactivation of B2 by high UVA irradiance does not seem to be effective for bacterial eradication in this study.